Integrating the Philosophy of Tri Hita Karana into Indonesian language material provision - Relin, Institut Hindu Dharma Negeri Denpasar, Binawati, Sariani. Ni Wayan, Rasna, I Wayan, Sudiana, I Gusti Ngurah, (Opción, 2019)
The aim of the study is to investigate the philosophy of Tri HitaKarana into Indonesian language material provision. The design wasmixed: in terms of its objective, it was descriptive using a surveytechnique, while in terms of data collection, it was qualitative. Theresults of the study showed that Tri Hita Karana philosophy is veryrelevant to be integrated into Indonesian material provision for first andsecond grades at primary school. In conclusion, the IndonesianTextbook with the Contextual Approach is appropriate and may beaccepted to be used and to be disseminated.